BP: synthesis and properties of boron phosphide. (11th July 2016) - Woo, Katherine; Lee, Kathleen; Kovnir, Kirill
Abstract: Cubic boron phosphide, BP, is notorious for its difficult synthesis, thus preventing it from being a widely used material in spite of having numerous favorable technological properties. In the current work, three different methods of synthesis are developed and compared: from the high temperature reaction of elements, Sn flux assisted synthesis, and a solid state metathesis reaction. Structural and optical properties of the products synthesized from the three methods were thoroughly characterized. Solid state metathesis is shown to be the cleanest and most efficient method in terms of reaction temperature and time. Synthesis by Sn flux resulted in a novel Sn-doped BP compound. Undoped BP samples exhibit an optical bandgap of ∼2.2 eV while Sn-doped BP exhibits a significantly smaller bandgap of 1.74 eV. All synthesized samples show high stability in concentrated hydrochloric acid, saturated sodium hydroxide solutions, and fresh aqua regia .